Hubungan antara Kompetensi Profesional dengan Hasil Belajar Keterampilan pada Kegiatan Ekstrakurikuler - Cici Anggrestu Harini; Irmawita Irmawita (Universitas Negeri Padang, 2022)
This research is motivated by the low learning outcomes of students' skills in participating in extracurricular activities in randai skills at SMA Negeri 1 Padang Ganting, Tanah Datar Regency. The cause of the low learning outcomes of this skill is due to the low professional competence of the instructor in learning activities. This study aims to describe the relationship between professional competence, describe student skills learning outcomes, and see the relationship between professional competence and randai skills learning outcomes in extracurricular activities at SMA Negeri 1 Padang Ganting, Tanah Datar Regency. This type of research is quantitative with a correlational technique. The population of this study were all students who took part in Randai extracurricular activities and the research sample used the Random Sampling technique. This is done through the use of a technique in the form of a questionnaire. The data analysis technique is the percentage formula and Spearman rho correlation. The results showed that the professional competence of instructors in Randai extracurricular activities was low, and student learning outcomes in Randai extracurricular activities were still low, and there was a significant relationship between professional competence and randai skills learning outcomes in extracurricular activities at SMA Negeri 1 Padang Ganting. Where in order for instructors to be able to develop professional competence in the process of randai activities so that the achievement of learning outcomes for students' skills is increased